Duplicate Left-Sided Vagus Nerve: Intraoperative Imaging, Management, and Placement - Zacharewski, Nicholas; Killory, Brendan D. (Journal of Neurological Surgery Reports, 2023)
Introduction Duplicate cranial nerves are fundamentally rare anatomical variants. Few case reports have documented cranial nerve duplication. One previous case report has reported a vagus nerve with a smaller secondary accessory nerve component. We present the first reported case of duplicate vagus nerves identical in size and thickness with otolaryngological diagnostic confirmation.Case Description A 25-year-old woman with seizures refractory to medical management decided to undergo placement of a vagus nerve stimulator. During carotid sheath microdissection, two parallel nerve tracts were identified. The two nerves were identical in size and width. Proximal dissection confirmed that the two nerves were independent of one another and neither was a branching segment. To confirm duplicate vagus nerves, otolaryngology was consulted intraoperatively and the duplicate nerves were verified. The vagus nerve stimulator was placed in typical fashion around the medial nerve.Conclusion This is the first reported case of duplicate vagus nerves identical in size and with confirmation by otolaryngology. The authors would like to highlight the operative management of the vagus nerve stimulator placement as well as integrity of the diagnostic conclusions based on size, further dissection, and specialist consultation.
Keywords: vagus nerve; duplicate; seizure; vagus nerve stimulator; microdissection